Registration of 'TAM 113' Wheat. Issue 1 (6th December 2012) - Rudd, Jackie C.; Devkota, Ravindra N.; Baker, Jason A.; Ibrahim, Amir M.; Worrall, David; Lazar, Mark D.; Sutton, Russell; Rooney, Lloyd W.; Nelson, Lloyd R.; Bean, Brent; Duncan, Robert; Seabourn, Brad W.; et al.
Abstract : 'TAM 113' (Reg. No. CV‐1081, PI 666125), a hard red winter wheat ( Triticum aestivum L.) cultivar with experimental designation TX02A0252, was developed and released by Texas AgriLife Research in 2010. TAM 113 is an F5 –derived line from the cross TX90V6313/TX94V3724 made at Vernon, TX in 1995. Both TX90V6313 and TX94V3724 are Texas experimental lines derived from the crosses TAM 200"S"/TX78A3345‐V34 and U1254‐1‐8‐1‐1/'TAM 202' (PI 561933), respectively. TAM 113 is an awned, medium maturing, semidwarf wheat with white glumes. It was released primarily for its excellent grain‐yield potential in both irrigated and dryland environments of the Texas High Plains; for its resistance to leaf rust (caused by Puccinia triticina Eriks.), stripe rust (caused by P. striiformis Westend.), and stem rust (caused by P. graminis Pers.:Pers f. sp. tritici Eriks. & E. Henn.); and for its good milling and exceptional bread‐baking characteristics. TAM 113 has a similar area of adaptation and grain‐yield potential as 'TAM 111' (PI 631352) and 'TAM 112' (PI 643143). However, compared with TAM 111, it has better leaf rust resistance and better bread‐baking qualities, and compared with TAM 112, it has better resistance to leaf and stripe rusts. TAM 113, with better milling and baking characteristics and resistance to leaf, stripe, and stem rusts, will provide a good complement to other hard red winter wheat cultivars for wheat producers in the southern Great Plains.